Hematopoietic Stem Cells of Bone Marrow and Their Total RNA in Rat Liver Regeneration - Nina Onishchenko; Murat Shagidulin; Zalina Gonikova; Alla Nikolskaya; Ludmila Kirsanova; Artem Venediktov; Ksenia Pokidova; Egor Kuzmin; Natalia Kuznetsova; Igor Kozlov; Dmitry Telyshev; Natalia Kartashkina; et al. (Applied Sciences)
Hematopoietic stem cells derived from bone marrow are known to induce tissue repair. Their mechanisms to induce liver regeneration are not clear and may have numerous adverse effects. We compared the regenerative potential of intact hematopoietic stem cells (iHSCs), their total RNA, and apoptotic hematopoietic stem cells (aHSCs) in liver damage. Male Wistar rats (n = 40 per group) experienced a 75% liver resection and received single intraperitoneal injections of saline (control group), iHSCs, aHSCs, or total RNA of iHSCs. We recorded animal survival, liver mass, blood markers of liver cell lysis and function (albumin, aminotransferases, alkaline phosphatase), and liver histological features: mitotic index and expression of markers for proliferation and apoptosis (caspase-9, caspase-3, and Ki-67). We assessed the survival with the log-rank test and used Wilcoxon and t tests for the other parameters. Animals of all HSC- or RNA-treated groups survived until the end of the experiment with full blood marker recovery (p = 0.037). The liver mass enlarged mostly after apoptotic hematopoietic stem cells and total RNA. Mitotic index peaked in the group of total RNA with a lower but earlier increase for the aHSC group, and Ki-67 proliferation for the total RNA group was the highest (all the differences were significant with p values ˂ 0.05). We found the aHSCs and total RNA of iHSC group to be the most efficient for liver reparation. Total RNA from HSCs is preferred for further liver regeneration studies.